If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6(3x + 3) = -198 Reorder the terms: 6(3 + 3x) = -198 (3 * 6 + 3x * 6) = -198 (18 + 18x) = -198 Solving 18 + 18x = -198 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-18' to each side of the equation. 18 + -18 + 18x = -198 + -18 Combine like terms: 18 + -18 = 0 0 + 18x = -198 + -18 18x = -198 + -18 Combine like terms: -198 + -18 = -216 18x = -216 Divide each side by '18'. x = -12 Simplifying x = -12
| -10=0.8y+6 | | -5x+4=-3x-2 | | 6x-3+2x=-67 | | 6x-3+2x=-64 | | 4(6x+2)=-112 | | -6x+1=5x+45 | | -23=3x+x+1 | | -7x-8=-1 | | 6(2x-1)=8x-2 | | 9x+5=4x+50 | | -x+9=-6+2x | | 0.85x+3y=0 | | -3x+4=-12+5x | | 2-x=-4x-10 | | -1+7x=5x-23 | | 6x-33=-x-5 | | 35000+250x=14 | | -2x+6=7x-21 | | 7x+7=-2x-11 | | -6+2x=-3x+29 | | 3(x)+3=24 | | 14.95+.13m=.39m-15 | | -6(4+6x)=-240 | | -4(1x+1)=24 | | 4(4+x)=32 | | 5+3x+x=-31 | | .39m-15=50 | | -16=2x+6x+8 | | x+12=-21 | | 5(3-4x)=-185 | | 0.5(8p+1)=13 | | 932x-x^2-195547=0 |